Photocatalytic degradation of dyes using one-step synthesized silica nanoparticles. (2021) - Biradar, Abhijit I.; Sarvalkar, Prashant D.; Teli, Shivanand B.; Pawar, C.A.; Patil, P.S.; Prasad, Neeraj R.
Graphical abstract: Schematic route diagram of one step synthesis of Silica nanoparticles. Highlights: Synthesis of silicon oxide based employing sol–gel method. Degradation of dye methylene blue and methyl orange. Abstract: Silica nanoparticles are synthesized by one step simple, rapid and cost effective sol–gel method using methyltrimethoxysilane (MTMS) as precursor. Synthesized silica nanoparticles are characterized by UV–Visible spectroscopic techniques, XRD and FE-SEM. From UV curve the maximum absorbance observed was at the wavelength 297 nm which indicates formation of silica nanoparticles. The FE-SEM analysis showed the larger size of nanoparticles is due to agglomeration of silica nanoparticles. The X-ray diffraction pattern indicate the structure of the silica nanoparticles. FT-IR spectra of silica nanoparticles are indicative of the stretching vibration of Si-O-Si bonds and Si-OH vibration respectively. TGA indicates the final degradation temperature of silica nanoparticles are near about 515 °C temperature. Photo degradation process is carried out by employing different dyes along with UV irradiating at pH-7. Photodegradation of both (10 ppm) methylene blue and methyl orange with 1.5 g/dm 3 SiO2 photocatalyst dose accomplished around 98 and 95% degradation in 90 min at 25 °C with pH-7. Finally, it can be concluded that silica nanoparticles support to the photo degradation of methylene blue and methyl orange. Hence nanoparticles synthesized using sol–gel method can be used for degradation of various industrial pollutants dyes.